The Conspiracy Theory/Vaccine Hesitancy nexus as rhetorical boundary work. A critical analysis of the production of scientific ignorance in literature reviews - Stocco, Nicola (PARTECIPAZIONE E CONFLITTO, 2023)
With the Covid-19 outbreak the request for useful knowledge to inform policy measures rapidly escalated. On the verge of infodemics, vaccine hesitancy and conspiracy theories have been individuated as major threats to society which need rapid responses. In this context of uncertainty, literature reviews are a great way to retrieve useful knowledge from the large and dispersed amount of knowledge produced in the last two years. Nevertheless, the structural process of reviewing is not a neutral process of evidence retrieval and can lead to the deformation of initial knowledge through synthesis and simplification. Furthermore, the boundary work in the review process, if not properly critically assessed, can polarize the distinction between scientists and non-experts. Drawing from STS literature on boundary work and scientific ignorance production, this article critically analyzes 12 literature reviews regarding the nexus between conspiracy theory and vaccine hesitancy. The results highlight how the rhetorical construction of the ignorance areas leads to the neglected arguments in the form of an implicit elitist discourse which reproduce the deficit model of policy intervention through the preference for the psychological explanation. Furthermore, the uncritical assumption of the rightfulness of the evidence retrieval leads to polarization in the construction of otherness and depoliticization of agency. The implications are discussed, along with examples of more creative and emancipative reviews.